THE CONSTRUCTION AND CONTESTATION OF ISLAMIC IDENTITY OF THE BAJO PEOPLE IN WAKATOBI ISLANDS, SOUTH EAST SULAWESI, INDONESIA - Benny Baskara; Irwan Abdullah; Djoko Suryo (Humaniora, 2014)
On the one one hand, the Bajo people are well-known as ‘the sea people’ who have their own indigenous belief system – belief in the Lord of the Sea. On the other hand, they also acknowledge themselves as Muslims. Thus, the religious identity of the Bajo people reflects a unique combination of Islamic teachings and their indigenous beliefs. This unique combination is not only expressed in their religious life, in their rituals and worship practices, but also in the values found in their customary practices (adat) as a guiding system for their life. This paper examines the construction and contestation of the religious identity of the Bajo people, especially how they construct their identities in relation to their natural, social, and religious environments. The contestation of the Bajo religious identity covers three aspects: the contestation of the Islam of ‘the sea people’ against the Islam of ‘the land people’, the contenstation of the ‘official’ Islam against the ‘traditional’ Islam, and the challenges of modernity, especially the commodification of the Bajo religious expressions. This contestation, in turn, reconstructs their religious identity into a more adaptive one.